Indigenous knowledge and use of medicinal plants for ethnoveterinary within the North West Province, South Africa - Ndou, Rendani Victress; Materechera, Simeon Albert; Mwanza, Mulunda; Otang-Mbeng, Wilfred; Ijane, Mooki Fabridge (Frontiers in Veterinary Science, 2023)
Ethnoveterinary medicine (EVM) has been used by local South African communities for centuries. However, the knowledge of EVM is under threat due to the influence of Western medicine and acculturation. This study aimed to document the knowledge of ethnoveterinary medicinal plants in four villages within the Mahikeng Local Municipality to help preserve this valuable knowledge. The study used a qualitative research approach and targeted practitioners and holders of ethnoveterinary knowledge in four villages. Participants were recruited using key informants and snowball techniques, and in-depth interviews were conducted using semi-structured interview schedules. The data collected was analyzed thematically, and herbarium specimens were prepared from medicinal plants during field walks and sent to the South African National Biodiversity Institute (SANBI) for identification. The study documented the use of thirty-one (31) medicinal plant species, with Senna italica (sebetebete) emerging as the most frequently used species for multiple animal health indications. The most common diseases treated using EVM were gala (general malaise due to bile reflux) and retained placenta. Participants strongly agreed on the cultural significance of plants for treating five animal diseases, including coughs and diarrhea. Although the study revealed a high level of trust in ethnoveterinary medicine among participants, they expressed concern regarding the loss of this knowledge due to the influence of Western medicine and acculturation. The study concluded that the indigenous knowledge and use of ethnoveterinary medicine was prevalent among livestock owners in the communities of the North West Province, and more studies need to be conducted in other areas to preserve this valuable knowledge.